Asymmetric Hydrogenation of Heteroarenes with Multiple Heteroatoms - Chen, Zhang-Pei; Zhou, Yong-Gui (Synthesis, 2016)
Enantiopure heterocyclic architectures containing two or more heteroatoms in the ring system have attracted considerable attraction due to this motif playing a role of great importance in asymmetric synthesis and the pharmaceutical chemistry. This review focused on recent advances in the homogeneous asymmetric hydrogenation of heteroarenes with multiple heteroatoms, which provide an efficient and practical method to structural diverse chiral heterocyclic compounds.1 Introduction2 Asymmetric Hydrogenation of Five-Membered-Ring Heteroarenes2.1 Imidazoles and Oxazoles2.2 Pyrazole Derivatives2.3 Benzisoxazoles3 Asymmetric Hydrogenation of Six-Membered-Ring Heteroarenes3.1 Quinoxalines3.2 Quinazolines3.3 Pyrimidines3.4 Pyrazines4 Asymmetric Hydrogenation of Fused Nitrogen Heteroarenes4.1 Heteroarenes Containing a Ring-Junction Nitrogen4.2 Heteroarenes Containing a Fused Pyridine Ring5 Conclusions and Outlook
Keywords: hydrogenation; enantioselectivity; heteroarenes; heterocycles; asymmetric catalysis